2015
DOI: 10.1002/jbm.a.35532
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB decoy oligodeoxynucleotide inhibits wear particle‐induced inflammation in a murine calvarial model

Abstract: Wear particles induce periprosthetic inflammation and osteolysis through activation of nuclear factor kappa B (NF-κB), which up-regulates the downstream target gene expression for proinflammatory cytokines in macrophages. It was hypothesized that direct suppression of NF-κB activity in the early phases of this disorder could be a therapeutic strategy for preventing the inflammatory response to wear particles, potentially mitigating osteolysis. NF-κB activity can be suppressed via competitive binding with doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 25 publications
(56 reference statements)
2
37
0
Order By: Relevance
“…The numbers of infiltrated macrophages and activated osteoclasts were reduced by decoy ODN treatment, but there were no significant effects on osteoblast differentiation. Together with our previous in vitro and in vivo studies [8, 12, 13], we demonstrated that NF-κB is a highly potential therapeutic target for peri-prosthetic osteolysis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The numbers of infiltrated macrophages and activated osteoclasts were reduced by decoy ODN treatment, but there were no significant effects on osteoblast differentiation. Together with our previous in vitro and in vivo studies [8, 12, 13], we demonstrated that NF-κB is a highly potential therapeutic target for peri-prosthetic osteolysis.…”
Section: Discussionsupporting
confidence: 81%
“…CD11b+ cells were manually counted under a fluorescence microscope (Axio Observer 3.1, Zeiss, Oberkochen, Germany) in 3 randomly selected fields of view. Osteoblasts and osteoclasts were determined as previously described [13]. In brief, osteoblasts were identified by anti-alkaline phosphatase (ALP) antibody (R&D, Minneapolis, MN) with the use of Avidin-biotin complex (Vector Laboratories) immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs can modulate osteoclast activation through paracrine regulation . The expression of RANKL and OPG is highly correlated with NF‐κB activity in MSCs . To investigate whether increased NF‐κB activity in aged MSCs is associated with impaired paracrine regulation, we examined RANKL and OPG mRNA expression in the MSCs in growth or osteogenic media (Days 1, 3, 7, 10, 14, 17, and 21).…”
Section: Resultsmentioning
confidence: 99%